Multi-techniques in the Spanish translation of euphemisms in Chinese classical works of the Ming and Qing dynasties - Yazhi, Cai (Sinología hispánica. China Studies Review, 2021)
In this article, we show the results of a study on the translation into Spanish of euphemisms in three classical Chinese novels. Through our analysis, it has been confirmed that there are three predominant techniques in translation, which are literal translation, euphemistic equivalent, and explicitness. When comparing the euphemistic degree, we found that there is a tendency towards explicitness in all three translations. Regarding the foreignizing or domesticating tendency, we found that Jin Ping Mei tends to be more foreignizing, and the other two translations are more domesticating. We think that the reasons for these differences are due to, firstly, the fact that the distributions of the areas of the euphemism in the three works are different, and, secondly, to the fact that each translator has his or her own style and objectives when translating.